2020
DOI: 10.1042/bsr20194296
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different concentrations of gold nanoparticles on growth performance, toxicopathological and immunological parameters of broiler chickens

Abstract: The present study aimed to evaluate what dosage of gold nanoparticles (GNPs) would improve growth performance, antioxidant levels and immune defense in broiler chickens. The experiment was carried out on 90 one-day-old mixbred Cobb chicks. The birds were allocated into three groups with three replicates. Group (1) kept as a negative control. Groups (2) and (3) received 5, 15 ppm GNPs via drinking water weekly for 35 days of chicks’ life. Blood samples were collected at 8, 15, 22 and 36 days for oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Microscopic grading and scoring were performed to document lesion severity of the examined organs in different treated groups. The grading criteria for degenerative, necrotizing, and inflammatory lesions were assessed as none, slight, mild, moderate, and severe as follow; 0 (normal histology), 1 (<25%), 2 (25:50%), 3 (50:75%), 4 (>75% tissue damage) according to method described by Hassanen et al [ 27 ]. While grading scheme for multifocal lesions assessed according to the method documented by Hassanen et al [ 28 ] as follow: (0) no foci; (1) <3 foci; (2) 3–6 foci; (3) 7–12 foci; (4) >12 foci.…”
Section: Methodsmentioning
confidence: 99%
“…Microscopic grading and scoring were performed to document lesion severity of the examined organs in different treated groups. The grading criteria for degenerative, necrotizing, and inflammatory lesions were assessed as none, slight, mild, moderate, and severe as follow; 0 (normal histology), 1 (<25%), 2 (25:50%), 3 (50:75%), 4 (>75% tissue damage) according to method described by Hassanen et al [ 27 ]. While grading scheme for multifocal lesions assessed according to the method documented by Hassanen et al [ 28 ] as follow: (0) no foci; (1) <3 foci; (2) 3–6 foci; (3) 7–12 foci; (4) >12 foci.…”
Section: Methodsmentioning
confidence: 99%
“…A study involving the immune organs of broiler chickens has confirmed that addition of 15 ppm AuNPs to drinking water has caused recognizable oxidative damage to blood, histopathological changes, up-regulation of IL-6, expression of Nrf2 gene, fragmentation of DNA, significant decrease in antibody titer against avian influenza (AI) and newcastle disease (ND) [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…The applications of nanotechnology in livestock and poultry production include optimizing the digestive efficiency, enhancing the immunity, and improving the performance [ 2 ]. Gold nanoparticles can boost antioxidant capability, immunity, and efficiency in poultry [ 3 ] while chromium nanoparticles increased skeletal muscle mass and improved pork quality [ 4 ]. Silver nanoparticles can be used in poultry production as an alternative to the use of antibiotic growth promoter [ 5 ].…”
Section: Introductionmentioning
confidence: 99%